The employment of real-time polymerase chain reaction for analysis of canine meat in meatball products for halal authentication analysis - Rumiyati, Rumiyati; Arini, Rien Larasati; Purwanto, Purwanto; Rohman, Abdul (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Meatballs are a popular meat-based food consumed widely in Indonesian society. However, the issue of unethical substitution of halal meatballs with non-halal meats, particularly pork and canine meat (CM), has emerged. The existence of non-halal meats, including CM, in food products is prohibited in Islam, necessitating the development of reliable analytical techniques for their identification. In this study, we designed species-specific primers (SSPs) targeting the D-loop region of mitochondrial DNA for CM meatball product identification. Materials and Methods: The study was commenced by creating specific primers for canine DNA using Integrated DNA Technologies software and subsequently performing DNA isolation. The designed primers were then subjected to comprehensive evaluation using RT-PCR, including specification, linearity, limit of detection, efficiency, and repeatability. Results: The results indicated that the primer D-Loop 443 (forward: 5’-GGG ACA TCT CGA TGG ACTA ATG-3’, reverse: 5’-GCG GTC ATA GAT GAG TGA TAG C-3’) designed and validated in silico using primer-basic local alignment search tool nucleotide (BLAST) program from NCBI accurately identified canine DNA when the optimal annealing temperature was set at 57.5oC. The real-time PCR technique utilizing the D-loop 443 primer exhibited the ability to amplify canine DNA down to a minimum quantity of 100 pg, with an efficiency value of 91.8%, a correlation coefficient (R) of 0.990, and a precision value (RSD) of 0.30%. Conclusion: The SSP-based RT-PCR method developed is a versatile and efficient tool for detecting CM in meatballs. Its implementation helps maintain consumer trust and addresses concerns regarding the substitution of halal meats with non-halal alternatives. Adv. Vet. Anim. Res., 11(2): 247-253, June 2024 http://doi.org/10.5455/javar.2024.k770